PENGELOLAAN KEUANGAN NEGARA - Paulina Y Amtiran; Aldarine Molidya (Universitas Nusa Cendana, 2020)
According to Law Number 17 of 2003 concerning State Finance, the President as the Head of Government holds the power to manage state finances as part of government power and power over the management of state finances is used to achieve state goals. However, to assist the Head of Government's duties, this power is delegated to the Minister of Finance, the Minister / head of the institution as the Budget User / Property User of the state ministries / institutions he leads and to the governor / regent / mayor as the head of the regional government.Financial management stages consist of planning, implementation, administration, reporting, accountability and supervision. Everything has been regulated in Law No.17 of 2003 on State Finance. In Law Number 17 of 2003 concerning State Finance, particularly articles 1 and 2, it is explained that what is meant by State Finance is all the rights and obligations of the state that can be valued in money, as well as everything in the form of money or in the form of goods that can be made state property related to the implementation of these rights and obligations. Keywords: Management Of State Finances, Rights And Obligations